2020
DOI: 10.3390/ma13020399
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Complex Nanostructured Thin Films Based on Titanium for Industrial Applications

Abstract: Titanium-based composites—titanium and silver (TiAg) and titanium and carbon (TiC)—were synthesized by the Thermionic Vacuum Arc (TVA) method on substrates especially for gear wheels and camshaft coating as mechanical components of irrigation pumps. The films were characterized by surface morphology, microstructure, and roughness through X-ray Diffraction (XRD), Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Small-Angle Neutron Scattering (SANS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The principle of the TVA is based on the combination of the anodic arc with a powerful electron gun system. It is a versatile method for performing multimaterial processing, such as in the case of alloy/composite thin films at a nanometric scale [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The principle of the TVA is based on the combination of the anodic arc with a powerful electron gun system. It is a versatile method for performing multimaterial processing, such as in the case of alloy/composite thin films at a nanometric scale [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…From the pictures reported, the variations of the topography of the surface CTRL respect to TEST are noticeable. From the height panel, the Nanoscope analysis 1.8 software (Bruker, Milan, Italy) is able to evaluate the roughness [37]. The AFM observations have shown that the TEST group was characterized by an average roughness (Ra) of 109.6 ± 35.7 nm and 367 ± 116.9 nm (Ra) for the CTRL (Figure 1).…”
Section: Atomic Force Microscopy Measurementsmentioning
confidence: 99%
“…[18] They include by Thermionic Vacuum Arc (TVA) Technology layers for fusion application, hard coatings, low-friction coatings, biomedicalapplicable films, materials for optoelectronics and for solid-state batteries. [19][20][21][22][23][24] The purpose of our work is to fabricate C-Ti multilayer nanostructures with certain mechanical and electrical properties determined by the content of TixCy and Ti phases Such nanostructures are relatively easy to obtain being essentially aletrnative layers of C and Ti deposited on the Si substrate at different temperature and bias voltages. The aim was highlight the TixCy and Ti phases by Raman measurements and electron microscopy as well as by coefficient of friction and electrical conductivity measurements.…”
Section: Introductionmentioning
confidence: 99%